The role of the state in shaping and protecting national identity - Bodrožić Đuro (Srpska Politička Misao)
In this paper, we are talking about the historical roots of the nation state. In order to understand the meaning of an ideal, it is necessary to know its history, which also applies to the national ideal. By nation we mean people who know themselves in their country. The idea of the state is what transforms a people, understood as a cultural concept, into a politically active force that we know as a nation. In order for a nation to be considered free, not only civil liberties in the state embodied in equality before good laws are sufficient, but also freedom, embodied un equality with other states, which is in its independence. National independence is needed by peoples in order to ensure that foreigners do not take advantage of them economically, plunder and exploit them, and do not subjugate them spiritually. Both economic and spiritual development imply freedom. There is no denying that the cultural development of a country and a people is deeply and inseparably linked with their national freedom. The state does not create a nation by infusing a single consciousness and will into a random multitude that would be acquired within the state borders, but it largely ensures the contrtion of factors that form the national will by ensuring the concentration of those factors. There are numerous examples of peoples that survived of their state, but there are no ehamples of the formation of a people being completed without a state structure. We cite reasons that indicate that the national state is the best form of political organization because it has proven to be the most suitable political form for preserving individual and collective freedom.